Behavioral Drivers of Tax Evasion Negotiation Love of Money Knowledge and Moral Reasoning in Indonesia - Pramudianti, Mira; Abidin, Khoirul (AGUSPATI Research Institute, 2026)
This study aims to understand tax evasion as a moral-psychological-religious negotiation process, not merely as a legal violation or a rational-economic decision. This study fills a gap in the literature that has been dominated by quantitative and rational-economic approaches, using an interpretive paradigm and a qualitative approach of interpretive phenomenology. The research informants consisted of 14 individual taxpayers and business actors who were purposively selected based on varying levels of love of money, tax knowledge, and religiosity. Data were collected through semi-structured interviews and document analysis, then analyzed using thematic analysis. The results show that tax evasion is interpreted as a moral dilemma negotiated through the interaction between the orientation of love of money, tax knowledge, and faith. Love of money acts as a driver of ethical rationalization that increases tolerance for practices in the legal gray area. Tax knowledge is ambivalent, as it can encourage compliance while also being a tool for moral justification. Religiosity does not function as an absolute barrier to tax evasion, but as an internal moral mechanism that gives rise to inner conflict, spiritual reflection, and a process of value negotiation. This research develops a conceptual understanding that tax evasion is the result of a dynamic interaction between psychological, cognitive, and spiritual factors within the taxpayer.